Dampak Tiktok Terhadap Gaya Hidup Remaja Perempuan - Risky Azizah; Revina Sinta Ananda; Andhita Risko Faristiana (Student Scientific Creativity Journal, 2023)
The era of globalization means an era where technology is experiencing rapid development. Developments that can be felt by people in various parts of the world are information and communication technology. The rapid development of this globalization era also has an impact on the rapid development of social media which has various advantages and different features. One of them is social media TikTok. The interest of teenagers in using social media TikTok has caused these teenagers to flock more and more to share important and unimportant things such as sharing the latest news with each other while things that are not important such as the occurrence of racism or blasphemy between humans to cases of bullying. Based on the background above, the author wants to discuss what are the impacts of social media TikTok on adolescent behavior in the era of globalization. Here the author uses a qualitative method which conducts a literature study of several journals.